The Effect Of Adding Tempeh Dregs And Moringa Leaves On Protein Content in Catfish Meatballs: An Alternative High-Protein Food For Underweight Children Under Five Years Old - Anugrah Linda Mutiarani; Rizki Nurmalya Kardina (Universitas Nahdlatul Ulama Surabaya, 2022)
Basic Health Research in 2018 revealed that 13.4% of children under five years oldwere underweight. Providing high-protein foods such as meatballs can be an alternativeproblem-solving. Several ingredients (vegetable and animal protein) can be added toenrich protein. This study aims to determine the effect of adding tempeh dregs, andMoringa leaves on the protein content in catfish meatballs. This study was anexperimental study with a completely randomized design (CRD) which formulatedcatfish, tempeh dregs, and Moringa leaves into four treatments with four repetitions.The formula in making meatballs were catfish 100% in the P0 group, catfish 60% +tempeh dregs 30% + moringa leaves 10% in the P1 group, catfish 60% + tempeh dregs20% + 20% Moringa leaves in the P2 group, and 100% catfish + 10% tempeh dregs +30% Moringa leaves in the P3 group. Meanwhile, the observation parameter was proteincontent. The data collection technique was carried out by proximate analysis of proteincontent with the Kjeldahl method. Data analysis used normality and homogeneity test,ANOVA test, and Least Significant Difference. The ANOVA test obtained p=0.000(p<0.05). Thus, there were significant differences in protein content in catfish meatballsbetween the control and the treatment group, except in P3. The Least SignificantDifference Test showed that the highest protein content was 9.0975% in the treatmentwith the formula 60% catfish meat, 30% tempeh dregs, and 10% Moringa leaves. Inconclusion, adding tempeh